The mid Upper Palaeolithic of European Russia: chronology, culture history and context: a study of five Gravettian backed lithic assemblages - Reynolds, N (2014)
This thesis examines the Mid Upper Palaeolithic (MUP) of Russia (ca. 30,000–20,000 14C BP). During this time, as in the rest of Europe, the principal archaeological industry is known as the Gravettian. However, in Russia two other industries, the Streletskayan and the Gorodtsovian, are also known from the beginning of the MUP. Historically, there have been significant problems integrating the Russian MUP record with that from the rest of Europe. The research described in this thesis concentrates on backed lithic assemblages (including Gravette points, microgravettes, other backed points and backed bladelets) from five Russian Gravettian sites: Kostenki 8 Layer 2, Kostenki 4, Kostenki 9, Khotylevo 2 and Kostenki 21 Layer 3. These are studied from an explicitly Western European theoretical perspective, using standard techno-typological methods to construct typological groupings and describe the variation between and within sites. Alongside this, new radiocarbon dates from several sites Kostenki 8 Layer 2, Kostenki 4 and Borshchevo 5) were obtained. These radiocarbon dates are critically analysed alongside published dates and unpublished dates made available to this research. The results of the research constitute a new culture history for the Russian MUP. Each stage of the MUP is dated and described, and the uncertainties in our knowledge outlined. One new lithic index fossil is defined and two others are re-assessed. The Russian record is compared with the contemporary archaeological record elsewhere in Europe, in order to describe large-scale synchronic variation and changes through time in the homogeneity and regionalisation of material culture. The relationship between these dynamics and climate change are discussed.